Detection of delamination in laminated composites with limited measurements combining PCA and dynamic QPSO. (August 2015) - Rao, A. Rama Mohan; Lakshmi, K.; Kumar, S. Krishna
Highlights: Proposed a new damage diagnostic technique for detection of delamination in laminated composite structures. Proposed algorithm is developed combining FRF, PCA and dynamic quantum PSO algorithm. Integrated an optimal sensor placement algorithm to test the proposed algorithm with limited measurements. A new dynamic quantum PSO algorithm is proposed to solve the inverse problem associated with damage assessment. Abstract: This paper presents an output only damage diagnostic algorithm based on frequency response functions and the principal components for health monitoring of laminated composite structures. The principal components evaluated from frequency response data, are employed as dynamical invariants to handle the effects of operational/environmental variability on the dynamic response of the structure. Finite element models of a laminated composite beam and plate are used to generate vibration data for healthy and damaged structures. Three numerical examples include a laminated composite beam, cantilever plate made of carbon–epoxy and a laminated composite simply supported plate. Varied levels of delamination of laminated composite plies and matrix cracking at varied locations in the plies are simulated at different spatial locations of the structure. Numerical investigations have been carried out to identify the spatial location of damage using the proposed principal component analysis (PCA) based algorithm. In order to limit the number of sensors on the structure, an optimal sensor placement algorithm based on PCA is employed in the present work and the effectiveness of the proposed algorithm with a limited number of sensors is also investigated. Finally, the inverse problem associated with the detection of delamination and matrix cracking is formulated as an optimization problem and is solved using the newly developed dynamic quantum particle swarm optimization (DQPSO) algorithm. Studies carried out and presented in this paper clearly indicate that the proposed SHM scheme can robustly identify the instant of damage, spatial location, the extent of delamination and matrix cracking even with limited sensor measurements and also with noisy data.